Low ADAMTS‐13 activity and the risk of coronary heart disease – a prospective cohort study: the Rotterdam Study. (3rd October 2016) - Sonneveld, M. A. H.; Kavousi, M.; Ikram, M. A.; Hofman, A.; Rueda Ochoa, O. L.; Turecek, P. L.; Franco, O. H.; Leebeek, F. W. G.; de Maat, M. P. M.
Abstract : Essentials An association between ADAMTS‐13 and coronary heart disease (CHD) has been suggested. 5688 participants ≥ 55 years from the Rotterdam Study without a history of CHD were included. Over a median follow‐up time of 9.7 years, 456 individuals suffered from CHD. Low ADAMTS‐13 activity was associated with an increased CHD risk. Summary: Background: The metalloprotease ADAMTS‐13 cleaves high‐molecular‐weight von Willebrand factor multimers into smaller, less procoagulant forms. Low ADAMTS‐13 activity is associated with an increased risk of ischemic stroke but its pathogenic role in coronary heart disease (CHD) is unclear. Objectives: We aimed to determine the association between ADAMTS‐13 activity and the risk of CHD in a large prospective population‐based cohort study. Methods: A total of 5688 participants of the Rotterdam Study, a population‐based cohort study involving individuals aged ≥ 55 years without a history of CHD, were included. ADAMTS‐13 activity was measured by the FRETS‐VWF73 assay and VWF:Ag levels by ELISA. We assessed the association between ADAMTS‐13 activity, VWF:Ag levels and CHD using Cox proportional hazard regression analysis, adjusting for cardiovascular risk factors. Results: Over a median follow‐up time of 9.7 years, 456 individuals suffered from CHD. A low ADAMTS‐13 activity (quartile 1) was associated with an increased CHD risk (HR 1.42, 95% CI 1.07–1.89) compared with the reference highest quartile. Conclusions: Low ADAMTS‐13 activity is associated with an increased risk of CHD in the elderly, independently of VWF and established cardiovascular risk factors.